Nanoarchitectonics with improved supercapacitive performance of jering‐derived porous activated carbon electrodes in aqueous electrolyte - Sunil, Vaishak; Salehan, Shahira Shaura; Ganesh, Gayathry; Rasidi, Roslan; Karnan, M.; Shetty, Manjunath; Samantray, R.; Jose, Rajan; Izan Izwan, Misnon (Springer Berlin Heidelberg, 2024)
The global shift from non-renewable to renewable energy sources demands advancements in energy storage solutions to effectively mitigate carbon footprints. Towards this direction, this study envisages the utilisation of activated carbon (AC) derived from jering pods (JP) synthesised at three different temperatures as supercapacitor (SC) electrode material. The physicochemical properties of the material were studied using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), and nitrogen (N₂) gas adsorption studies. In a half-cell study conducted in a 6 M aqueous KOH electrolyte, the best-performing AC delivered a specific capacitance (CS) of 301 F/g at 0.5 A/g. A full device assembly demonstrated a CS of 71 F/g at 0.5 A/g, energy density (ED), and power density (PD) of ~ 14 Wh/kg and ~ 9000 W/kg, respectively. The device showed excellent cyclic stability of ~ 96% of its initial capacitance after 3000 cycles. These findings present the viability of the valorisation of JP as a sustainable electrode material for SC application.